Gender diversity and senior leadership in academic dentistry: Female representation at the dean position in the United States. Issue 4 (6th November 2021) - Bompolaki, Despoina; Pokala, Sai Vishnu; Koka, Sreenivas
Abstract: Purpose/objectives: The purpose of this study was to calculate the male to female dean ratio in the US dental schools, assess whether the dean's gender is affected by specific school characteristics (such as geographic location or class size), and determine whether the dean's gender affects the percent of women in the school leadership team. Methods: Each US school's website was reviewed to capture the name and gender of each dean and others holding assistant, associate or vice dean positions. All data were entered in an Excel database (Microsoft Excel 2016) and analyzed using a statistical analysis software program (IBM SPSS Statistics, v26; IBM Corp). The level of significance was set to α  = 0.05. Results: The male to female dean ratio (approximately 5:1) differed significantly from the hypothesized ratio 1:1 ( z  = 5.22, p  < 0.001). Mean class size ( χ 2  = 0.869, p  = 0.351) and school funding source ( χ 2  = 0.430, p  = 0.512) did not differ between schools with a male versus female dean. The percentage of women in the school's leadership team was higher in schools with a female dean ( U  = 151, p  = 0.004). Conclusions: In the US dental schools, there is one female dean for every five deans who are male, indicating underrepresentation of women at the highest role in academic leadership. Schools with female deans tend to have more women in other administrative roles as well. Change is needed in order to promote equity, diversity, and inclusion in academic dentistry.